Accrual Quality, Realized Returns, and Expected Returns: The Importance of Controlling for Cash Flow Shocks - Ogneva, Maria (The Accounting Review, 2012)
ABSTRACT This paper develops a simple methodology based on the earnings response coefficient framework that allows decomposing realized returns into cash flow shocks and returns excluding cash flow shocks. I find that stocks with poor (good) accrual quality were on average subject to relatively lower (higher) cash flow shocks over the past 37 years. These lower (higher) cash flow shocks offset the higher (lower) expected returns of poor (good) accrual quality firms. After excluding cash flow shocks, future realized returns are negatively associated with accrual quality. The premiums pertaining to accrual quality are both statistically and economically significant in standard asset-pricing tests when cash flow shocks are excluded by firm-specific return decomposition. Overall, this paper provides evidence on the existence of a priced accrual quality risk factor, and underscores the importance of controlling for cash flow shocks in asset-pricing tests that use realized returns.